Hydrogel-chitosan and polylactic acid-polycaprolactone bioengineered scaffolds for reconstruction of mandibular defects: a preclinical in vivo study with assessment of translationally relevant aspects - Ferrari, Marco; Taboni, Stefano; Chan, Harley H. L.; Townson, Jason; Gualtieri, Tommaso; Franz, Leonardo; Ruaro, Alessandra; Mathews, Smitha; Daly, Michael J.; Douglas, Catriona M.; Eu, Donovan; Sahovaler, Axel; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Reconstruction of mandibular bone defects is a surgical challenge, and microvascular reconstruction is the current gold standard. The field of tissue bioengineering has been providing an increasing number of alternative strategies for bone reconstruction.In this preclinical study, the performance of two bioengineered scaffolds, a hydrogel made of polyethylene glycol-chitosan (HyCh) and a hybrid core-shell combination of poly(L-lactic acid)/poly(𝜀-caprolactone) and HyCh (PLA-PCL-HyCh), seeded with different concentrations of human mesenchymal stem cells (hMSCs), has been explored in non-critical size mandibular defects in a rabbit model. The bone regenerative properties of the bioengineered scaffolds were analyzed by in vivo radiological examinations and ex vivo radiological, histomorphological, and immunohistochemical analyses.The relative density increase (RDI) was significantly more pronounced in defects where a scaffold was placed, particularly if seeded with hMSCs. The immunohistochemical profile showed significantly higher expression of both VEGF-A and osteopontin in defects reconstructed with scaffolds. Native microarchitectural characteristics were not demonstrated in any experimental group.Conclusions: Herein, we demonstrate that bone regeneration can be boosted by scaffold-and seeded scaffold-reconstruction, achieving, respectively, 50% and 70% restoration of presurgical bone density in 120 days, compared to 40% restoration seen in spontaneous regeneration. Although optimization of the regenerative performance is needed, these results will help to establish a baseline reference for future experiments.